Labour associations in their relation to the state - Finlay, T.A. (Statistical and Social Inquiry Society of Ireland, 1912)
The individuals who engage in the same industry are drawn together by the force of common interests, and where they are not dominated by a power strong enough to prevent combination among them they will unite to defend and promote the interests common to their class. It was so in Greece and Rome; it was so in the mediaeval states, and it is so to-day, And wherever this phenomenon has manifested itself it has given rise to problems which have caused grievous perplexity to statesmen. These problems are with us now, and it is not exaggerating their gravity to say that their solution will tax to the full whatever resources of statesmanship we possess. I propose to offer in this paper a brief account of some forms in which this problem has presented itself in earlier stages of the economic evolution of Europe, selecting one from Rome, another from a typical mediaeval state, and a third from our own country within the modern period which begins with what has been styled the Industrial Revolution.
President's address [1911/1912]
Read, November 28th, 1911
Keywords: Trade unions; Guilds; Industrial relations; 314.15